2005
DOI: 10.5432/ijshs.3.296
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Application of the Bio-Electrical Impedance Method for the Estimation of Tendon Elongation

Abstract: This study aimed to investigate the applicability of the bio-electrical impedance (BI) method for the estimation of tendon elongation due to muscle contraction. We applied the BI method with a cylindrical model to the muscle-tendon complex (MTC). While subjects performed ramp isometric elbow flexion up to 80% of maximal voluntary contraction (MVC), BI was measured using a bio-electrical impedance muscle analyzer. Simultaneously, tendon elongation was also determined directly by ultrasonography. The amount of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…When a joint is fixed at a given joint angle, a muscle-tendon unit is constant in length. However, a tendon is stretched during an isometric contraction (Ohta et al, 2005) and consequently muscle length is decreased. Given that muscle volume hardly changes by contraction (Baskin and Paolini, 1967), the aforementioned phenomenon can result in an increase in muscle CSA at certain sites.…”
Section: Discussionmentioning
confidence: 99%
“…When a joint is fixed at a given joint angle, a muscle-tendon unit is constant in length. However, a tendon is stretched during an isometric contraction (Ohta et al, 2005) and consequently muscle length is decreased. Given that muscle volume hardly changes by contraction (Baskin and Paolini, 1967), the aforementioned phenomenon can result in an increase in muscle CSA at certain sites.…”
Section: Discussionmentioning
confidence: 99%
“…The contraction-induced increase in elbow flexor thickness is apparently associated with the corresponding elongation of the tendon and disappearance of muscle slackness with contractions (Akagi et al, 2008). The amount of tendon elongation is positively related to the contraction intensity (Ito et al, 1998;Ohta et al, 2005) and the extent to which the muscle slackness disappears is expectedly influenced by the contraction intensity, suggesting that the elbow flexor MAs might be dependent on the contraction intensity. Moreover, since elbow flexor MAs at rest change depending on the elbow joint angle (Amis et al, 1979;Gonzalez et al, 1996;Koo et al, 2002), the effect of the contraction intensity on MAs of elbow flexors might vary across different elbow joint angles.…”
mentioning
confidence: 95%
“…In addition, the individual differences in muscle CSA at each site during isometric contractions were generally larger than those at rest as shown in Figure 3. In the previous study cited above (16), the elongation of the distal tendon of the biceps brachii was shown to be highly individual during isometric contractions (the CVs for 14 young men were approximately 34-47% during 10-80%MVC). This may be a reason for the large differences in muscle CSA at each site under the contracted condition because the elongation of the distal tendon of the biceps brachii is a factor in the contraction-induced change in the CSA distribution pattern along the upper arm length as described above.…”
Section: Discussionmentioning
confidence: 95%
“…Consequently, the elongation of the tendon induced by isometric contractions affects the above CSA distribution pattern. It has been shown that, compared with at rest, the contraction-induced increase in the length of the distal tendon of the biceps brachii is 2.0, 3.3, 6.0, 7.5, and 8.5 mm during 10%MVC, 20%MVC, 40%MVC, 60%MVC and 80% MVC, respectively (16). Thus, the tendon elongation appears prominently during low-intensity contraction and comes close to its peak above a relatively high contractile level, likely contributing to the present results on the contraction-induced change in muscle CSA.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation